Pengaruh Penggunaan Metode Pembelajaran Aktif Terhadap Peningkatan Pemahaman Mata Pelajaran Pendidikan Agama Islam di MAN 2 Kota Bengkulu - Ilvia Anggun Dwi Mutiara; Verly Tri Seftiani; Intan Meida Ababil; Qolbi Khoiri (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This study aims to analyze the influence of the use of active learning methods on improving the understanding of Islamic religious education subjects in MAN 2 Bengkulu City. Using a quantitative method with a pseudo-experimental design approach. The research sample of 60 students was divided into two groups, namely the experimental group and the control group. The results of the study showed that the use of active learning methods had a positive and significant influence on the improvement of understanding of Islamic religious education subjects, as seen from the results of the experiment as follows: the average posttest score for the experimental group using the active learning method was 82.5, while the control group that used the traditional lecture method only obtained an average post-test score of 65.2. And the results of the ttest showed a value of p = 0.001 (p<0.05), this means that there was a significant difference between the experimental group and the control group in the understanding of Islamic religious education subjects. So it can be suggested, to improve the understanding of Islamic religious education subjects, increase the use of active learning methods in madrasas.Keywords: The use of active learning methods, understanding Islamic religious education materials, MAN 2 Kota Bengkulu.Abstak: Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan metode pembelajaran aktif terhadap peningkatan pemahaman mata pelajaran pendidikan agama Islam di MAN 2 Kota Bengkulu. Menggunakan metode kuantitatif dengan pendekatan desain eksperimen semu. Sampel penelitian 60 siswa dibagi dalam dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Hasil penelitian menunjukkan bahwa penggunaan metode pembelajaran aktif memiliki pengaruh yang positif dan signifikan terhadap peningkatan pemahaman mata pelajaran pendidikan agama Islam, terlihat dari hasil eksperimen sebagai berikut rata-rata nilai post-test untuk kelompok eksperimen yang menggunakan metode pembelajaran aktif adalah 82,5, sementara kelompok kontrol yang menggunakan metode ceramah tradisional hanya memperoleh rata-rata nilai post-test sebesar 65,2. Dan hasil uji t-test menunjukkan nilai p = 0,001 (p<0,05), ini berarti terdapat perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol dalam pemahaman mata pelajaran pendidikan agama Islam. Sehingga dapat disarankan, untuk meningkatkan pemahaman mata pelajaran pendidikan agama Islam, maka tingkatkanlah penggunaan metode pembelajaran aktif di madrasah.Kata kunci: Penggunaan Metode Pembelajaran Aktif, Pemahaman Materi Pendidikan Agama Islam, MAN 2 Kota Bengkulu.